Perancangan dan Pembuatan Prototype Mesin CNC Laser Engravir Dengan Mikrokontroler sebagai Komunikasi Wireless - Tresna Umar Syamsuri; Rachmat Sucipto; Epiwardi (Elposys: Jurnal Sistem Kelistrikan, 2023)
To support the creative economy, creative ideas are needed which are then transformed into concrete reality. One of the concrete creative ideas is art craftsmen, for example, painting, sculpture, three-dimensional art, sculpture and many more. The promising craft today is the souvenir craft, which has various forms and functions. In this research, the authors specialize in the craft of engraved souvenirs where most of these craftsmen still work on their crafts using conventional media. The purpose of this research is to design and manufacture a prototype CNC Laser Engraver machine with a microcontroller with wireless data communication which is expected to help improve the quality of the production of souvenir craftsmen. The method used is an experimental method in the form of designing, manufacturing and testing the mechanical work of each linear axis of the CNC Laser Engraver machine. With this research it is hoped that a control system scheme for a prototype CNC Laser Engraver machine can be obtained, to be applied to a real CNC Laser Engraver machine. From the results of testing this machine prototype, some data was obtained, namely a machine with three axes of motion, a microcontroller for wireless communication, a laser module with a diode capacity of 1000 mW and a maximum work area of 38 mm x 38 mm x 20 mm, which can help small industries and businesses. small and medium enterprises in the production process of various forms of creative carvings for various materials